The Influence of Instagram and TikTok on E-commerce Purchase Decisions: Consumer Behavior Analysis using SEM-PLS - Rahman, Sofyan Fathur; Yasin, Ahmad; Renaldi, Faiza; Pudjiantoro, Tacbir Hendro (Jurnal Indonesia Sosial Sains, 2025)
Social media platforms such as TikTok and Instagram have significantly transformed how consumers interact with products and make purchasing decisions. This study aims to analyze the influence of social media usage and electronic word of mouth (e-WOM) on purchase decisions, with trust and consumer behavior serving as mediating variables. A quantitative, explanatory research design was employed. Data were collected from 164 respondents using purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results show that social media usage has a significant effect on consumer behavior and directly influences purchase decisions. Meanwhile, e-WOM does not have a direct effect on purchase decisions but contributes significantly through the mediating roles of trust and consumer behavior. Trust plays an essential role in linking e-WOM to consumer behavioral responses. Among all the tested relationships, consumer behavior emerged as the strongest predictor of purchase decisions. These findings emphasize the importance of digital marketing strategies that foster trust and strengthen behavioral engagement. The study also reinforces the theoretical relevance of the Stimulus–Organism–Response (S-O-R) and Uses and Gratification (U&G) models in the context of social commerce. Future studies are encouraged to explore additional mediating factors such as emotional engagement or platform-specific characteristics to improve the model’s predictive strength.